Host-guest chemistry of truncated tetrahedral imine cages with ammonium ions - Lauer, Jochen; Pang, Ziwei; Janßen, Paul; Rominger, Frank; Kirschbaum, Tobias; Mastalerz, Michael (ChemistryOpen, 2020)
Three shape-persistent [4+4] imine cages with truncated tetrahedral geometry with different window sizes were studied as hosts for the encapsulation of tetra-n-alkylammonium salts of various bulkiness. In various solvents the cages behave differently. For instance, in dichloromethane the cage with smallest window size takes up NEt4+ but not NMe4+, which is in contrast to the two cages with larger windows hosting both ions. To find out the reason for this, kinetic experiments were carried out to determine the velocity of uptake but also to deduce the activation barriers for these processes. To support the experimental results, calculations for the guest uptakes have been performed by molecular mechanics' simulations. Finally, the complexation of pharmaceutical interested compounds, such as acetylcholine, muscarine or denatonium have been determined by NMR experiments.